(untitled) (LEARNing Landscapes, 2014)
Professional development for teacher educators must recognize and account for how aspects of our pedagogies often run counter to institutional, managerial, and bureaucratic demands. We need professional development that nurtures our minds, hearts, and spirits, and that is congruent with our values. In this paper, three teacher educators who co-teach an intensive, interdisciplinary, inquiry-based semester in a secondary teacher education program, explore how collaborative approaches to narrative forms of inquiry and reflexive analysis supported them to enact their learning, as well as helped them to surface the situated, complex, and emergent aspects of their own—as well as their students’—identities.